Comparison of Tissue Preservation using Formalin and Ethanol as Preservative Formula - See Woan Shian; Arifin Soenggono; Sawkar Vijay Pramod (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Tissue preservation can be performed through embalming, by providing the chemical embalming fluid to the human remains. Formalin’s preservative formula is the foundation for modern methods of embalming. Unfortunately, this preservative formula has several disadvantages. While Ethanol’s preservative formula is a considerable agent to replace formalin’s preservative formula. The aim of this study was to compare the tissue preservation using formalin and ethanol as preservative formula.Methods: This study was carried out from September–October 2014 in the Laboratory of the Department of Anatomy, Faculty of Medicine, Universitas Padjadjaran. The study used the laboratory experimental method with consecutive sampling of 16 Wistar Rats. Thirty two soleus muscles and thirty two colons were collected and divided into two groups. Each group consisted of 16 soleus muscles and 16 colons. Group 1 was preserved with formalin’s preservative formula and Group 2 was preserved with ethanol’s preservative formula. The two groups were preserved for six weeks. The tissue’s color, consistency, odor and the growth of bacteria were determined before and after treatment.Results: Tissues preserved with ethanol’s preservative formula had better tissue preservation in the aspect of color and odor, compared with formalin’s preservative formula. Both preservative formulas showed no growth of bacteria in tissues but failed to retain the consistency. All the data were analyzed with Chi-square test.Conclusions: Ethanol’s preservative formula preserves better quality of tissue compared to formalin’s preservative formula. [AMJ.2016;3(3):359–63] DOI: 10.15850/amj.v3n3.880